The use of an inspiration-synchronized vibrating mesh nebulizer for prolonged inhalative iloprost administration in mechanically ventilated patients: an in vitro model - Otto, Matthias; Kropp, Yannik; Jäger, Evelyn; Neumaier, Michael; Thiel, Manfred; Quintel, Michael; Tsagogiorgas, Charalambos (Pharmaceutics, 2023)
Mechanically ventilated patients suffering from acute respiratory distress syndrome (ARDS) frequently receive aerosolized iloprost. Because of prostacyclin’s short half-life, prolonged inhalative administration might improve its clinical efficacy. But, this is technically challenging. A solution might be the use of inspiration-synchronized vibrating mesh nebulizers (VMNsyn), which achieve high drug deposition rates while showing prolonged nebulization times. However, there are no data comparing prolonged to bolus iloprost nebulization using a continuous vibrating mesh nebulizer (VMNcont) and investigating the effects of different ventilation modes on inspiration-synchronized nebulization. Therefore, in an in vitro model of mechanically ventilated adults, a VMNsyn and a VMNcont were compared in volume-controlled (VC-CMV) and pressure-controlled continuous mandatory ventilation (PC-CMV) regarding iloprost deposition rate and nebulization time. During VC-CMV, the deposition rate of the VMNsyn was comparable to the rate obtained with the VMNcont, but 10.9% lower during PC-CMV. The aerosol output of the VMNsyn during both ventilation modes was significantly lower compared to the VMNcont, leading to a 7.5 times longer nebulization time during VC-CMV and only to a 4.2 times longer nebulization time during PC-CMV. Inspiration-synchronized nebulization during VC-CMV mode therefore seems to be the most suitable for prolonged inhalative iloprost administration in mechanically ventilated patients.
Gesehen am 19.12.2023